2014
DOI: 10.1016/j.joca.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

NASHA hyaluronic acid vs methylprednisolone for knee osteoarthritis: a prospective, multi-centre, randomized, non-inferiority trial

Abstract: This study shows that single-injection NASHA was well tolerated and non-inferior to MPA at 12 weeks. The benefit of NASHA was maintained to 26 weeks while that of MPA declined. An injection of NASHA at 26 weeks conferred long-term improvements without increased sensitivity or risk of complications. STUDY IDENTIFIER: NCT01209364 (www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
77
2
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 26 publications
10
77
2
10
Order By: Relevance
“…Our results are consistent with studies of intra-articular NASHA injection for knee and hip OA,1418 showing a long duration of action and favorable tolerability. For example, a 26-week study comparing single-injection NASHA with methylprednisolone acetate in knee OA showed similar Western Ontario and McMaster Universities (WOMAC) OA pain index responder rates in the two study groups at 12 weeks, with the WOMAC pain effect size increasingly favoring NASHA between 12 and 26 weeks 18.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with studies of intra-articular NASHA injection for knee and hip OA,1418 showing a long duration of action and favorable tolerability. For example, a 26-week study comparing single-injection NASHA with methylprednisolone acetate in knee OA showed similar Western Ontario and McMaster Universities (WOMAC) OA pain index responder rates in the two study groups at 12 weeks, with the WOMAC pain effect size increasingly favoring NASHA between 12 and 26 weeks 18.…”
Section: Discussionsupporting
confidence: 91%
“…In general, while CSs have shown to be more effective (especially on pain control) in the short term (<1 month), better results have been reported with HA at subsequent evaluations, providing only a moderate effect after 26 weeks (8,12,17,(33)(34)(35)(36)(37)(38)(39). Furthermore, the efficacy of repeated injections of HA, after a previous course of either HA or CSs, has also been proved (37,40). However, other studies neglected the efficacy of HA (41-44), reporting only small or no differences compared with CSs.…”
Section: Rationale: Css Vs Hamentioning
confidence: 99%
“…Furthermore, HA is considered safe also after a previous course of HA injections (35,37,40). Despite this evidence, the safety profile of intra-articular HA injections has recently been questioned (43).…”
Section: Adverse Events and Safetymentioning
confidence: 99%
“…[25], в котором оценивалась эффективность однократной в/с инъекции высокомолекулярной синтети-ческой гиалуроновой кислоты и ГК (метилпреднизолон) у 442 больных ОА коленного сустава. Через 12 нед число от-ветивших на лечение по WOMAC-боль (уменьшение на >40%) в исследуемых группах не различалось (44,6 и 46,2% соответственно, т. е.…”
Section: %unclassified